A Tailored Catalyst for the Sustainable Conversion of Glycerol to Acrolein: Mechanistic Aspect of Sequential Dehydration. Issue 8 (8th July 2014) - Yun, Danim; Kim, Tae Yong; Park, Dae Sung; Yun, Yang Sik; Han, Jeong Woo; Yi, Jongheop
Abstract Developing a catalyst to resolve deactivation caused from coke is a primary challenge in the dehydration of glycerol to acrolein. An open‐macropore‐structured and Brønsted‐acidic catalyst (Marigold‐like silica functionalized with sulfonic acid groups, MS‐FS) was synthesized for the stable and selective production of acrolein from glycerol. A high acrolein yield of 73 % was achieved and maintained for 50 h in the presence of the MS‐FS catalyst. The hierarchical structure of the catalyst with macropores was found to have an important effect on the stability of the catalyst because coke polymerization and pore blocking caused by coke deposition were inhibited. In addition, the behavior of 3‐hydroxypropionaldehyde (3‐HPA) during the sequential dehydration was studied using density functional theory (DFT) calculations because 3‐HPA conversion is one of the main causes for coke formation. We found that the easily reproducible Brønsted acid sites in MS‐FS permit the selective and stable production of acrolein. This is because the reactive intermediate (3‐HPA) is readily adsorbed on the regenerated acid sites, which is essential for the selective production of acrolein during the sequential dehydration. The regeneration ability of the acid sites is related not only to the selective production of acrolein but also to the retardation of catalyst deactivation by suppressing the formation of coke precursors originating from 3‐HPA degradation.